The home country institutional quality and investor recognition benefits of cross listed firms: Evidence of cross listed firms from BRICS countries - Adeyanju, Adebiyi (Universitas Nahdlatul Ulama Surabaya, 2024)
While cross listing is an integral part of firm visibility, no attention has been drawn whether the firm home country institutional quality influences investor behaviour after foreign financial market integration. This study examined the relationship between the institutional quality of the firm home country and investor recognition of cross-listed firms from emerging markets countries. Using data of cross-listed firms from the BRICS bloc between 2000 to 2020, we find that changes in investor recognition of cross listed firms are strongly related to the signal of the institutional quality perceptions in the firm home country in the long and short run after foreign financial market integration. This study highlighted the significance of the information environment of the home country in explaining the Investor Recognition Hypothesis (IRH) of cross listing.